Prediction of Radiographic Damage in Early Arthritis by Sonographic Erosions and Power Doppler Signal: A Longitudinal Observational Study. Issue 6 (30th May 2013) - Funck‐Brentano, Thomas; Gandjbakhch, Frédérique; Etchepare, Fabien; Jousse‐Joulin, Sandrine; Miquel, Anne; Cyteval, Catherine; Lukas, Cédric; Tobón, Gabriel J.; Saraux, Alain; Boumier, Patrick; Goupille, Philippe; Bourgeois, Pierre; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the ability of ultrasonography (US) to predict radiographic damage in early arthritis. Methods ESPOIR is a multicentric cohort of early arthritis (i.e., ≥2 swollen joints between 6 weeks and 6 months). US synovitis in B mode, power Doppler (PD) mode, and erosions were searched on the second through the fifth metacarpophalangeal and fifth metatarsophalangeal joints according to Outcome Measures in Rheumatology definitions. Structural radiographic progression was assessed using the modified Sharp/van der Heijde erosion score (SHS) at baseline and 1 and 2 years. Predictive factors of erosive arthritis at 2 years and rapid radiographic progression (RRP) at 1 year (defined by change of SHS ≥5) were searched. Results A total of 127 patients were included, with a mean ± SD Disease Activity Score in 28 joints of 5.1 ± 1.3; 37.6% were anti–citrullinated protein antibody positive and 27.6% had typical rheumatoid arthritis (RA) erosions on radiographs. At 2 years, 42 patients (39.2%) had typical RA erosions. US erosions predicted radiographic evidence of erosive arthritis (odds ratio [OR] 1.44, 95% confidence interval [95% CI] 1.04–1.98). PD synovitis score was predictive of RRP at 1 year (OR 1.22, 95% CI 1.04–1.42). US erosions and PD synovitis scores were associated with change of SHS on linear regression. Of the 1, 184 analyzed joints, 105 (8.9%) had radiographic erosion at 1 year. At the joint level, baseline US erosions were predictive of the presence of radiographic erosions at 1 year (P < 0.001). The same trend was observed in the joints without radiographic erosions at baseline (P = 0.052). Conclusion US is useful to evaluate the potential severity of early arthritis: US erosions and PD‐positive synovitis have prognostic value to predict future radiographic damage.